Ongoing Voluntary Settlement and Independent Agency: Evidence from China - Feng, Jing; Ren, Xiaopeng; Ma, Xinran (Frontiers in Psychology, 2017)
Voluntary frontier settlement leads to independent agency. Since this type of research has not yet been implemented in ongoing voluntary settlement frontiers, we conducted several cultural tasks to investigate Shenzhen, known as China’s ongoing “South Frontier”, which is composed mostly of people that have emigrated from other Chinese provinces within the past 30 years. We hypothesized that residents of Shenzhen are more independent than those in other regions of Mainland China. As predicted, residents of Shenzhen scored higher than China inland residents in self-reported independent beliefs and scored lower in nepotism. The results indicate that, even in a short-term ongoing frontier, voluntary settlement is associated with independent agency.